The science of snacks: a review of dog treats - Calancea, Bogdan-Alexandru; Daina, Sorana; Macri, Adrian (Frontiers in Animal Science, 2024)
The global growth in canine population has led to a thriving market for pet food, especially treats sector. This review explores the growing market for canine treats, revealing a deep emotional connection between pet owners and their pets, evident in feeding practices. With six distinct categories of treats, meat-based treats dominate due to perceptions of naturalness and health, high-lighting an increased focus on dog nutrition and a preference for raw, locally sourced alternatives. However, labelling discrepancies and a lack of clear nutritional information present a challenge for owners looking for quality treats. Variations in nutritional values and sensory qualities of treats require informed choices to prevent excessive calorie consumption and potential health implications. Effective communication between the veterinarian and pet owners is crucial to adapting treats recommendations based on the individual needs of dogs, taking into account potential health risks and obesity. In conclusion, the use of treats provides several benefits such as positive reinforcement, promoting dental health and providing nutritional support for senior dogs. However, certain aspects that may limit their use should be considered, such as the risk of microbiological contamination, accidents related to incorrect administration, obesity and environmental impacts associated with treat production.